Chronopolitical Battles During Popular Unity in Chile (1970-1973): An Outline of Analysis [Las Batallas Cronopolíticas Durante la Unidad Popular en Chile (1970-1973): Un Esbozo de Análisis] - Faure-, A (Universidad Compultense Madrid, 2021)
This essay proposes an outline of a temporal analysis of a very important political conflict in the world history of the 20th century: the Chilean Popular Unity (1970-973). For this purpose, a review is made of part of the secondary literature on the Chilean experience based on two concepts forged and proposed that we have proposed to investigate the politicization of time: chronopolitical battles and momentum, understood as the dynamics of a social tempo on which one can act, by the ability to maintain this tempo in duration or to guide changes through an impulse. It is concluded that the Popular Unity project sought to accelerate the expansive momentum of this phase of Chilean history, which provoked discronies and dis-synchronies that forced the reactionary counter-offensive to break with this momentum. © 2021, Universidad Compultense Madrid. All rights reserved.